2012
DOI: 10.4103/0976-237x.94554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation of Hurler syndrome in a 7 year old child

Abstract: Mucopolysaccharidosis type I (MPS I H, Hurler syndrome) is a rare autosomal recessive inborn deficiency in the metabolism of glycosaminoglycans (GAGs) heparan sulfate and dermatan sulfate, resulting from deficiency of Alpha-L-iduronidase enzyme. This condition is characterized by accumulation of incompletely degraded glycosaminoglycans into various organs of body, which leads to impairment of organs and body functions. Such children appear nearly normal at birth; however, if left untreated, show a progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Radiographic features that have been reported include short mandibular rami with abnormal condyles; reports also include delayed eruption teeth related to the presence of multiple unerupted teeth with large thickened dental follicles secondary to excessive dermatan sulfate and collagen deposition. 3,[7][8][9][13][14][15][17][18][19][20][21][22][23][24][25][26][27] Notwithstanding, to date there are no studies comparing oral features of patients with mucopolysaccharidosis with controls without the disease. The evaluation of dental conditions in patients with MPS is scarce considering that in literature only clinical cases are described.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Radiographic features that have been reported include short mandibular rami with abnormal condyles; reports also include delayed eruption teeth related to the presence of multiple unerupted teeth with large thickened dental follicles secondary to excessive dermatan sulfate and collagen deposition. 3,[7][8][9][13][14][15][17][18][19][20][21][22][23][24][25][26][27] Notwithstanding, to date there are no studies comparing oral features of patients with mucopolysaccharidosis with controls without the disease. The evaluation of dental conditions in patients with MPS is scarce considering that in literature only clinical cases are described.…”
Section: ■ Resultsmentioning
confidence: 99%
“…3,7-9,13-15,17-27 Thick lips with an open mouth posture are also features associated with this syndrome. 3,7-9,13-15, [17][18][19][20][21][22][23][24][25][26][27] Few studies have reported the oral and dental changes in MPS patients. The reported alterations include a short and broad mandible, macroglossia, anterior open-bite, high arched palate with pronounced rugae, spaced dentition, lip hypotonia, gingival hyperplasia and enlargement of the alveolar process.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hurler's Syndrome (HS) [16,17] A defect in genetically controlled pathways of lysosomal degradation. Physical and mental deterioration…”
Section: No Dental Findingsmentioning
confidence: 99%